Distribusi Kekayaan dalam Islam: Telaah Kebijakan Rasulullah Saw dan Relevansi bagi Indonesia - Alhasanah, Nila; Latifah, Febri; Tofa, Dhea Khasyana; Afifah Dwi Putri Ritonga (JOVISHE : Journal of Visionary Sharia Economy, 2023)
Wealth distribution in Islam plays a crucial role in achieving social justice and equitable welfare. The wealth distribution policies implemented by Prophet Muhammad (PBUH) encompass principles of justice, humanity, and solidarity, with the aim of reducing social inequality and strengthening the economy of the ummah. Prophet Muhammad (PBUH) emphasized the importance of zakat, alms, charity, and waqf as primary instruments for distributing wealth, not only to meet the basic needs of the poor but also to empower them through more sustainable programs. The eight categories of zakat recipients (fakir, miskin, amil, muallaf, slave, gharimin, fisabilillah, and ibnu sabil) reflect Islam's concern for fulfilling the basic rights of individuals and ensuring fair wealth distribution. In Indonesia, the application of the wealth distribution principles taught by Prophet Muhammad (PBUH) remains relevant in addressing issues of poverty, social inequality, and community-based economic development. The management of zakat and waqf by institutions such as BAZNAS and the Indonesian Waqf Board (BWI) has made significant progress in utilizing these resources for economic empowerment and poverty alleviation. This article aims to examine the wealth distribution policies of Prophet Muhammad (PBUH) and analyze their relevance and challenges in the context of Indonesia today. The research findings indicate that the implementation of Islamic wealth distribution principles in Indonesia has the potential to strengthen social solidarity, reduce economic inequality, and build a more just and prosperous society.